Reforms in child and youth welfare - Karin Böllert (Social Work and Society, 2019)
Child and youth services are the social infrastructure of young people's growth and the support of their families, which includes welfare-regulated care, education and protection, promotion and participation services, with the goal of individual empowerment to develop self-determined life plans and welfare-oriented life practices as well as the structural enabling of social participation as expression of the perception of a public responsibility for equal opportunities for life and the reduction of social inequalities. It must be analyzed whether and with what political goals, the child and youth welfare service can meet this requirement.